Remediating Desmoplasia with EGFR‐Targeted Photoactivable Multi‐Inhibitor Liposomes Doubles Overall Survival in Pancreatic Cancer. Issue 24 (24th June 2022) - Obaid, Girgis; Bano, Shazia; Thomsen, Hanna; Callaghan, Susan; Shah, Nimit; Swain, Joseph W. R.; Jin, Wendong; Ding, Xiadong; Cameron, Colin G.; McFarland, Sherri A.; Wu, Juwell; Vangel, Mark; et al.
Abstract: Desmoplasia is characteristic of pancreatic ductal adenocarcinoma (PDAC), which exhibits 5‐year survival rates of 3%. Desmoplasia presents physical and biochemical barriers that contribute to treatment resistance, yet depleting the stroma alone is unsuccessful and even detrimental to patient outcomes. This study is the first demonstration of targeted photoactivable multi‐inhibitor liposomes (TPMILs) that induce both photodynamic and chemotherapeutic tumor insult, while simultaneously remediating desmoplasia in orthotopic PDAC. TPMILs targeted with cetuximab (anti‐EGFR mAb) contain lipidated benzoporphyrin derivative (BPD‐PC) photosensitizer and irinotecan. The desmoplastic tumors comprise human PDAC cells and patient‐derived cancer‐associated fibroblasts. Upon photoactivation, the TPMILs induce 90% tumor growth inhibition at only 8.1% of the patient equivalent dose of nanoliposomal irinotecan (nal‐IRI). Without EGFR targeting, PMIL photoactivation is ineffective. TPMIL photoactivation is also sixfold more effective at inhibiting tumor growth than a cocktail of Visudyne‐photodynamic therapy (PDT) and nal‐IRI, and also doubles survival and extends progression‐free survival by greater than fivefold. Second harmonic generation imaging reveals that TPMIL photoactivation reduces collagen density by >90% and increases collagen nonalignment by >10 3 ‐fold. Collagen nonalignment correlates with a reduction in tumor burden and survival. This single‐construct phototoxic, chemotherapeutic, and desmoplasia‐remediating regimen offers unprecedented opportunities to substantially extend survival in patients with otherwise dismal prognoses. Abstract : Desmoplasia in pancreatic ductal adenocarcinoma (PDAC) is one of most significant hurdles in effective management of the disease. Treating desmoplasia alone has proven to be unsuccessful in the clinic, thus necessitating transformative combination approaches. This study is the first to demonstrate that a desmoplasia‐remediating regimen using a single targeted and activable photodynamic‐chemotherapeutic construct doubles overall survival in orthotopic PDAC.